Corneal epithelial thickness mapping using Fourier‐domain optical coherence tomography for detection of form fruste keratoconus. Issue 4 (April 2015) - Temstet, Cyril; Sandali, Otman; Bouheraoua, Nacim; Hamiche, Taous; Galan, Alice; El Sanharawi, Mohamed; Basli, Elena; Laroche, Laurent; Borderie, Vincent
Abstract : Purpose : To determine whether optical coherence tomography (OCT) epithelial mapping can improve the detection of form fruste keratoconus. Setting : French National Eye Hospital, Paris 6 Pierre & Marie Curie University, Paris, France. Design : Retrospective comparative study. Methods : Eyes with normal corneas, form fruste keratoconus, moderate keratoconus, or severe keratoconus were assessed using Fourier‐domain OCT (RTVue 5.5), scanning‐slit corneal topography (Orbscan IIz), and rotating Scheimpflug camera (Pentacam Comprehensive Eye Scanner). Several parameters provided by the software or derived from elevation maps, OCT pachymetric maps, and OCT epithelium parameters were evaluated and compared between the 4 groups. Results : The study involved 145 eyes. There were no significant differences in the keratometry (K) value, inferior–superior value, keratoconus index, central K index, and topographic keratoconus classification indices between the form fruste keratoconus group and the control group ( P > .05). Form fruste keratoconic corneas had less epithelial thickness in the thinnest corneal zone than normal corneas, and greater epithelial thickness in the thinnest corneal zone than keratoconic corneas ( P < .005). The epithelial thickness in the thinnest corneal zone in form fruste corneas was located inferiorly ( P < .005) and corresponded with the zone of minimum epithelial thickness and maximum posterior elevation ( P < .005). The receiver operating characteristic curve analysis showed good overall predictive accuracy of the epithelial thickness in the thinnest corneal zone, with a 52 μm threshold value for discriminating form fruste keratoconic corneas from normal corneas. Conclusions : The epithelial thickness in the thinnest corneal zone and its location provided by the OCT epithelial mapping might be useful for the early diagnosis of form fruste keratoconus. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.